Association of serum Cystatin C with neuromyelitis optica spectrum disorders. (4th May 2018) - Shu, Y.; Zhang, L.; Chang, Y.; Li, R.; Sun, X.; Li, J.; Wu, H.; Yang, Y.; Peng, L.; Lu, Z.; Kermode, A. G.; Qiu, W.
Abstract : Background and purpose: The relationship between Cystatin C (CysC) and neuromyelitis optica spectrum disorders (NMOSD) is unknown. Methods: Serum CysC levels were measured in 105 Chinese patients with NMOSD (53 in relapse, 52 in remission) and 109 healthy controls (HCs). The association of CysC with NMOSD and its clinical and magnetic resonance imaging parameters were evaluated. Results: Cystatin C levels were significantly lower in patients with relapsing NMOSD than in those in remission ( P < 0.001) or HCs ( P < 0.05). CysC levels in NMOSD remission were higher than in HCs ( P = 0.002). CysC levels were positively associated with age and negatively associated with brain lesion numbers in relapsing NMOSD ( r = −0.252, P = 0.069). Conclusion: Our results indicate a reduced serum level of CysC in patients with relapsing NMOSD and an increased level in remission. Further studies on the role of CysC in NMOSD are warranted.